Green Eco-Soap Hand Wash - Anis Nur Syazwani Azhar,; Nur Sabrina Mohd Safarin,; Ab Razak, Siti Noraiza (Multidisciplinary Applied Research and Innovation, 2024)
Improper disposal and management of waste cooking oil (WCO) will cause various environmental, economic, and health problems. The development of eco soap hand wash not only serves as a green replacement to traditional goods, but it also helps decrease the environmental effect associated with inappropriate WCO discharge. The main focus of this project is to produce high-quality eco-hand soap using WCO as major raw material with additions of other ready ingredients. The technique used for this purpose was saponification using sodium chloride (NaCl), sodium hydroxide (NaOH) and potassium hydroxide (KOH) at different concentrations. The best liquid soap produced through this project was sample A2B2 where the proportion of NaCl and KOH in the soap are 10% and 60%, respectively. The sample A1C1 contain  the best proportion of NaCl and NaOH in solid soap production where the concentration of NaCl is 5% while NaOH is 20%.